NOD1 and NOD2: intracellular pattern recognition receptors implicated in gynaecological malignancies and their therapeutic potential - Yuanyuan Zhang; Duan Yang; Xinlu Liu (Gynecology and Obstetrics Clinical Medicine)
Nucleotide-binding oligomerisation domains (NODs) are pattern recognition receptors involved in the detection of intracellular pathogenic microorganisms and important members of the NOD-like receptor family. These cytoplasmic receptors play a crucial role in orchestrating the innate immune response and are implicated in the progression of various inflammatory disorders, as well as inflammation-related neoplasms. In this review, we summarised the recent developments in NOD1 and NOD2 studies with a particular focus on their role in gynaecological malignancies. These findings emphasise the critical and dynamic roles of NOD1 and NOD2 proteins in gynaecologic cancers and provide insights into integrative therapeutic strategies targeting the NOD-associated signalling cascades.